Factor Supporting Companies Performing Transfer Pricing - Nurjannah; Muh Haekal Yunus; Renaldi Renaldi; Munawir Munawir; Rafiqah Asaff (Jurnal Akuntansi, 2022)
This study examines the effect of taxes, tunneling incentives, and bonus mechanisms on transfer pricing. The population in this study is the financial statements of primary and chemical industry companies listed on the Indonesia Stock Exchange in the 2018-2020 period, totaling 64 companies obtained through the official website of the Indonesia Stock Exchange (www.IDX.co.id.) This study's sample was obtained using the purposive sampling method; the total sample is 39 data from 13 financial statements of the primary and chemical industry sector for three years. Secondary data was collected through the Indonesia Stock Exchange website and analyzed using Multiple Regression Analysis with the Ordinary Least Square model using the Eviews Version 12 software. The results found that the tax variable shows a positive and significant effect on the occurrence of transactions transfer pricing. Meanwhile, the variable tunneling incentive and the bonus mechanism have no significant effect on transfer pricing.